A Practical Synthesis of 2-{4-[4-Fluoro-3-(trifluoromethyl)phenyl]-2-(piperidin-4-yl)-1H-imidazol-1-yl}-N,N-dimethylethanamine - Vaid, Radhe K.; Spitler, Jeremy; Boini, Sathish; Henry, Kenneth; Jiansheng, Xu; Gao, Baitao; Lu, Xiaoquan (Synthesis, 2012)
A practical synthesis of the title compound was accomplished by hydrogenation of 2-{4-[4-fluoro-3-(trifluoromethyl)phenyl]-2-(pyridin-4-yl)-1H-imidazol-1-yl}-N,N-dimethylethanamine. The latter was obtained by N-alkylation of 4-{4-[4-fluoro-3-(trifluoromethyl)phenyl]-1H-imidazol-2-yl}pyridine. Treatment of N-{2-[4-fluoro-3-(trifluoromethyl)phenyl]-2-oxoethyl}isonicotinamide hydrochloride with ammonium acetate in acetic acid provided 4-{4-[4-fluoro-3-(trifluoromethyl)phenyl]-1H-imidazol-2-yl}pyridine. Coupling of 2-amino-1-[4-fluoro-3-(trifluoromethyl)phenyl]ethanone 4-methylbenzene sulfonate with pyridine 4-carboxylic acid using either T3P or EDCI-HOBt provided N-{2-[4-fluoro-3-(trifluoromethyl)phenyl]-2-oxoethyl}isonicotinamide hydrochloride.
Keywords: imidazole; EDCI; T3P; ammonium acetate; hydrogenation